P6.08 Offering sti testing in a community-based hiv prevention outreach progam. (8th July 2017) - Bruce, Joshua; Wagoner, Nicholas Van; Culver, Austin; Aaron, Kristal J; Pol, Barbara Van Der
Abstract : Introduction: STI testing is too often separated from HIV testing services and thus persons who may be at risk for STI are not adequately screening for infection. Data suggest that current STI infection is an indicator of elevated risk for HIV infection over a short period of time (e.g. 3 months). Therefore, detecting STI is important to both STI treatment and management and HIV risk-reduction. Methods: In October 2015 we began offering STI screening at Birmingham AIDS Outreach, a CBO that, among other activities, offers HIV testing, counselling and prevention services. Molecular testing for chlamydia, gonorrhoea and trichomonas was performed using self-obtained vaginal or male urine specimens as well as self-obtained oropharyngeal and anal swabs from any clients who wished to be screened at those sites. Here we report the case rates and the utility of testing both genital and extragenital samples. Results: 663 men and 341 women were screened in 15 months and 478 specimens from a total of 1148 visits were tested. 39 STI (chlamydia, gonorrhoea or trichomonas) were detected with a positive case rate of 32/663 (4.8%) and 7/341 (2.1%) for men and women, respectively. Among those with an STI, 1 had a positive HIV or syphilis result at the same visit (not all clients were tested for HIV and syphilis). Extragenital testing detected 22 cases of STI (18 rectal and 4 oropharyngeal) thus 56% if infections would not have been detected if screening was performed using only genital specimens. Conclusion: The case rates in this population of persons utilising HIV prevention services was higher than that seen in the general population in the US and was similar to rates seen at STD clinics in the state of Alabama. The clients of this CBO are not routine users of the local STD clinic and theses cases would have gone undetected if not for this program. Combining STI screening with HIV prevention is a critical to reducing the burden of both STI and HIV I at risk populations.